COMPREHENSIVE ANALYSIS OF DATA INTEGRATION STRATEGIES FOR SYNDROME SURVEILLANCE SYSTEMS - 1Mohammed Hussein Alyami, 2Saleh Hussein Alyami, 3Ali Yahya Almutyif, 4Mana Masoud Almansour, 5Khalid Mohammed Alduways, 6Ali Hassan Ai Mansour, 7Mana Ali Ai Mansour, 8Salem Mubarak Al Shahi (Chelonian Research Foundation, 2023)
Syndrome surveillance systems play a crucial role in monitoring public health by detecting and tracking outbreaks of infectious diseases and other health-related events... Data integration procedures are imperative to advance the viability and effectiveness of syndrome surveillance frameworks by coordinating and disentangling diverse data for time-intensive investigation. This comprehensive survey investigates different angles of information integration utilized in syndrome observation frameworks, counting syndrome surveillance information sources, integration strategies, information investigation procedures, and challenges. Fundamental discoveries highlight the significance of collaboration, the information age, high-level examination, and partner engagement within the public health utilization of information investigation. Clean drinking is accomplished by suggesting advancing data integration procedures to make strides in the opportuneness, precision, and convenience of surveillance frameworks in identifying and reacting to well-being problems. Keywords: Syndrome surveillance, data integration, public health, data sources, analytics.